Hubungan Hygiene Sanitasi dengan Kejadian Diare pada Masyarakat di Lingkungan II Gg Kolam Kelurahan Deli Tua Barat Kecamatan Deli Tua pada Tahun 2025 - Rangkuti, Rifka Adinda; Suriyani, Siti; Putri, Wanda Aprilia; Padang, Nita Rosa Br; Amirah, Nada (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Diarrhea is one of the environment-based diseases that remains a public health problem in Indonesia, especially in areas with poor hygiene and sanitation conditions. This study aims to determine the relationship between hygiene and sanitation with the incidence of diarrhea among the community in Lingkungan II Gg Kolam, Deli Tua Barat Subdistrict, Deli Tua District in 2025. This research used a quantitative method with a cross-sectional approach. A total of 55 respondents were selected using purposive sampling from a total population of 120 people. Data were collected through structured questionnaires and direct observation, then analyzed using the chi-square test with a 95% confidence level. The statistical test results showed a significant relationship between latrine facilities and the incidence of diarrhea (p = 0.050; OR = 0.306), as well as a highly significant relationship between hygiene behavior and the incidence of diarrhea (p = 0.000; OR = 0.089). The study concludes that improving the quality of environmental sanitation through the provision of proper latrine facilities and the promotion of hygiene behaviors such as regular handwashing with soap is essential to reduce the incidence of diarrhea.